Board size, chief risk officer and risk-taking in Islamic banks: role of shariah supervisory board(Saiz Lembaga Pengarah, Ketua Pegawai Risiko dan Pengambilan Risiko di Bank-bank Islam: Peranan Lembaga Penyeliaan Syariah) - Najwa, Nur Athirah; Ramly, Zulkufly; Haron, Razali (UKM Press, 2019)
This paper aims to examine the moderating effect of Shariah Supervisory Boards (SSBs) on the relationship between board size, Chief Risk Officer (CRO), and risk-taking of 24 Islamic banks (IBs) in Malaysia, Indonesia and Brunei from 2010 to 2015. This approach integrates the arguments of agency theory and resource dependence theory. The results of panel regression indicate that the appointment of a CRO as an executive board member reduces credit risk, implying that the appointment of a CRO as a risk expert in IBs enhances the management of risk and monitoring of risk-taking activities. Further, larger board is likely to reduce insolvency risk when an SSB has higher percentage of members with supervisory Shariah experience. Next, this study observes that larger SSB size and a higher percentage of members with Shariah supervision experience moderate the relationship between the CRO and insolvency risk. Overall, this study highlights the important role of board size, CRO and SSB in the risk-taking of Islamic banks, which have received little attention in the extant literature.